ANALISIS TINGKAT KEPERCAYAAN DIRI SAAT BERTANDING ATLET PENCAK SILAT UNIVERSITAS MUHAMMADIYAH SORONG - Nur Rahman; Agus Kurniadi; Istiyono; Muh Mawardi; La Robi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Confidence is one of the psychological aspects that plays an important role in supporting the performance of pencak silat athletes when competing. This study aims to analyze the level of confidence when competing in pencak silat athletes of the University of Muhammadiyah Sorong. The research uses a quantitative descriptive approach with a survey method. The subjects of the study were 30 pencak silat athletes who were determined by total sampling technique. The instrument used was in the form of a confidence questionnaire which included indicators of confidence in one's abilities, emotional control during competitions, optimism in facing opponents, and courage to make decisions. Data were analyzed using descriptive statistics in the form of averages, percentages, and categorization. The results showed that 46.7% of athletes were in the high confidence category, 40% in the medium category, and 13.3% in the low category. Indicators of confidence in one's abilities have the highest average scores, while emotional control during competitions has the lowest average scores. The conclusion of the study shows that the level of confidence of pencak silat athletes at the University of Muhammadiyah Sorong is generally in the medium to high category, but the aspect of emotional control still needs special attention through a structured mental training program.